2010
DOI: 10.1038/jes.2010.41
|View full text |Cite
|
Sign up to set email alerts
|

PBDE exposure from food in Ireland: optimising data exploitation in probabilistic exposure modelling

Abstract: Polybrominated diphenyl ethers (PBDEs) are a class of brominated flame retardants added to plastics, polyurethane foam, electronics, textiles, and other products. These products release PBDEs into the indoor and outdoor environment, thus causing human exposure through food and dust. This study models PBDE dose distributions from ingestion of food for Irish adults on congener basis by using two probabilistic and one semi-deterministic method. One of the probabilistic methods was newly developed and is based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 49 publications
0
24
1
Order By: Relevance
“…Table 3 shows the MOS derived for the individual congeners BDE-47, -99, -153, -183 and -209 and for the total dose of congeners BDE-47, -99, -100, -153 and -154, which are the major components of commercial penta mixtures (Konstantinov et al 2008). All derived MOS for the 97.5th quantile of the doses as presented in Trudel et al (2010) (for comparison we use the external doses presented therein, i.e. before uptake of the substance into the body) are larger than 1 Â 10 5 with the lowest MOS at 1.6 Â 10 5 for BDE-99 (endpoint impaired spermatogenesis).…”
Section: Sensitivity Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…Table 3 shows the MOS derived for the individual congeners BDE-47, -99, -153, -183 and -209 and for the total dose of congeners BDE-47, -99, -100, -153 and -154, which are the major components of commercial penta mixtures (Konstantinov et al 2008). All derived MOS for the 97.5th quantile of the doses as presented in Trudel et al (2010) (for comparison we use the external doses presented therein, i.e. before uptake of the substance into the body) are larger than 1 Â 10 5 with the lowest MOS at 1.6 Â 10 5 for BDE-99 (endpoint impaired spermatogenesis).…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…Therefore, the doses derived in this study together with doses derived in a previous study (Trudel et al 2010) are compared to the relevant NOAEL or LOAEL (lowest-observed-adverse-effect level) identified in the EU risk assessment reports by following the margin of safety (MOS) concept (van Leeuwen and Vermeire 2007). The risk assessment is performed for effects on the liver caused by the commercial mixtures of pentaBDE (product name: DE-71) and decaBDE, and for effects on reproduction caused by octaBDE: Individual congener data are compared to the relevant NOAEL, LOAEL or BMDL (benchmark dose lower confidence level) for potential effects on the liver, neurodevelopment, reproduction and impaired spermatogenesis as identified by a number of different researchers (for details, see Supporting Information, Section 4).…”
Section: Risk Assessmentmentioning
confidence: 99%
See 3 more Smart Citations